Emancipatory Education Of Paulo Freire From An Islamic Educational Perspective: A Conceptual Analysis Of Liberation And Critical Consciousness - Madkan; Fauziyah; Aslamiyah, Siti Suwaibatul (Interdisciplinary Journal of Social Sciences, 2025)
This study aims to analyse Paulo Freire's concept of emancipatory education about Islamic educational values, particularly in the aspects of liberation and critical consciousness. The main focus of this research is to explore the alignment between Freire’s problem-posing education approach and the principles of Islamic education, which emphasise the development of individuals who are knowledgeable, ethical, and socially responsible. This study employs a descriptive qualitative approach using library research methods, drawing on various academic sources including books, nationally accredited journals (SINTA), and reputable international journals such as those indexed by Scopus. Data analysis is conducted through data reduction, presentation, and conclusion drawing using a comparative approach between Freire's theory and the Islamic educational perspective. The findings indicate that Freire’s critical pedagogy shares fundamental values with Islamic principles such as tawhid (monotheism), justice, and social responsibility. Freire’s idea of education as a process of liberation aligns with the aims of Islamic education, which seeks to free individuals from ignorance and oppression toward spiritual and social enlightenment. The value of critical consciousness in Islam is reflected in Qur'anic verses such as Surah Az-Zumar: 9 and Al-Baqarah: 269. This study opens opportunities for integrating critical pedagogy into a more humanistic and transformative contemporary Islamic education..